Mono- to tetra-alkyl ether cardiolipins in a mesophilic, sulfate-reducing bacterium identified by UHPLC-HRMSn: a novel class of membrane lipids - Hopmans, Ellen C.; Grossi, Vincent; Sahonero-Canavesi, Diana X.; Bale, Nicole J.; Cravo-Laureau, Cristiana; Sinninghe Damsté, Jaap S. (Frontiers in Microbiology, 2024)
The composition of membrane lipids varies in a number of ways as adjustment to growth conditions. Variations in head group composition and carbon skeleton and degree of unsaturation of glycerol-bound acyl or alkyl chains results in a high structural complexity of the lipidome of bacterial cells. We studied the lipidome of the mesophilic, sulfate-reducing bacterium, Desulfatibacillum alkenivorans strain PF2803 T by ultra-high-pressure liquid chromatography coupled with high-resolution tandem mass spectrometry (UHPLC-HRMS n ).This anaerobic bacterium has been previously shown to produce high amounts of mono-and di-alkyl glycerol ethers as core membrane lipids. Our analyses revealed that these core lipids occur with phosphatidylethanomamine (PE) and phosphatidylglycerol (PG) head groups, representing each approximately one third of the phospholipids. The third class was a novel group of phospholipids, i.e. cardiolipins (CDLs) containing one (monoether/triester) to four (tetraether) ether-linked saturated straight-chain or methyl-branched alkyl chains. Tetraether CDLs have been shown to occur in archaea (with isoprenoid alkyl chains) but have not been previously reported in the bacterial Domain. Structurally related CDLs with one or two alkyl/acyl chains missing, so-called monolyso-and dilyso-CDLs, were also observed. The potential biosynthetic pathway of these novel CDLs was investigated by examining the genome of D. alkenivorans. Three CDL synthases were identified; one catalyzes the condensation of two PGs, the other two are probably involved in the condensation of a PE with a PG. A heterologous gene expression experiment showed the in vivo production of dialkylglycerols upon anaerobic expression of the glycerol ester reductase enzyme of D. alkenivorans in E. coli.Reduction of the ester bonds probably occurs first at the sn-1 and subsequently at the sn-2 position after the formation of PEs and PGs.